You and I : living and learning. Career explorations for youth - Newfoundland and Labrador Association for Adult Education (Memorial University of Newfoundland. Educational Television Centre, 1983)
In this episode host Rosemary MacDonald speaks with Patricia Ralph to discuss a program called Career Explorations for Youth, aimed at young adults between the ages of 18-25 who either just finished school or who were previously employed but are currently unemployed. Its goal is to prepare young people for the workforce, to help them get a job and to hold onto it. Minor distortion in places.